STRATEGI PEMASARAN UDANG VANNAMEI PADA TAMBAK UDANG PT. CENDANA PRIORITAS LESTARI KABUPATEN BENGKULU TENGAH - Tito Irwanto; Herry Novrianda; Dora Wasi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2018)
Tito Irwanto, Herry Novrianda, Dora Wasiati Ayu Juniarti; The purpose of this study is to know the strengths, weaknesses, opportunities and threats. The most appropriate strategy for vannamei shrimp farms is to use SO strategies, using all the power to exploit opportunities. Methods of data collection using questionnaires by spreading questions to respondents. Result of research of IFAS and EFAS, hence power owned at PT. CendanaPrioritas Lestari Bengkulu Tengah is 19.94 while the weakness is 5.7 if the internal quadrant factor is 19.94 - 5.7 = 14.24 the opportunity of the strategy is 17.08 for the threat so that 10 is the external quadrant factor 17 , 08 - 10 = 7.08 so that it is in quadrant 1 in SWOT analysis.Key Words: Marketing Strategy, SWOT Analysis.